Serine hydroxymethyl transferase is required for optic lobe neuroepithelia development in Drosophila. - Silva, E.A.B.; Venda, A.M.; Homem, C.C.F. (Development, 2023)
Cell fate and growth require one-carbon units for the biosynthesis of nucleotides, methylation reactions and redox homeostasis, provided by one-carbon metabolism. Consistently, defects in one-carbon metabolism lead to severe developmental defects, such as neural tube defects. However, the role of this pathway during brain development and in neural stem cell regulation is poorly understood. To better understand the role of one carbon metabolism we focused on the enzyme Serine hydroxymethyl transferase (Shmt), a key factor in the one-carbon cycle, during Drosophila brain development. We show that, although loss of Shmt does not cause obvious defects in the central brain, it leads to severe phenotypes in the optic lobe. The shmt mutants have smaller optic lobe neuroepithelia, partly justified by increased apoptosis. In addition, shmt mutant neuroepithelia have morphological defects, failing to form a lamina furrow, which likely explains the observed absence of lamina neurons. These findings show that one-carbon metabolism is crucial for the normal development of neuroepithelia, and consequently for the generation of neural progenitor cells and neurons. These results propose a mechanistic role for one-carbon during brain development.